Syntactic complexity in assessing young adolescent EFL learners' writings: Syntactic elaboration and diversity. (July 2020) - Bi, Peng; Jiang, Jingyang
Abstract: This study investigates the relationship between syntactic complexity and writing quality, measured by both syntactic elaboration and diversity, based on 410 narrative essays of adolescent beginner and intermediate Chinese EFL learners. Syntactic elaboration measures were analyzed by the L2 Syntactic Complexity Analyzer. Syntactic diversity was measured by the corrected type-token ratio of dependency relations, a new metric proposed by this study. Three regression analyses were conducted, each with writing scores as an outcome variable, but the syntactic elaboration model employed traditional syntactic elaboration measures as explanatory variables; the syntactic diversity model employed the syntactic diversity measure; and the combined model used all of the measures. The results show that 1) syntactic elaboration measures account for 36.6% of the variance in writing scores, with mean length of sentence, complex nominals per clause, and clauses per T-unit as the best predictors; 2) the syntactic diversity measure alone could predict 32.1% of the variance in writing scores; 3) the combined model, including both syntactic elaboration and syntactic diversity measures, could explain 45.3% of the variance (the largest amount of variance in the study) in writing scores.